Development and Validation of the Model Minority Stereotype-Response Scale - Suh, Han Na; Rice, Kenneth G.; Osborne, Alexis (The Counseling psychologist, 2024)
The model minority stereotype (MMS) has had a direct and significant impact on Asian Americans and their internal processes, like other stereotypes attributed to a group of people (e.g., stereotype threat; Steele & Aronson, 1995). In this article, we describe the development and validation of a measure named the Model Minority Stereotype-Response Scale (MMS-RS), which is designed to assess the responses Asian Americans experience when faced with the MMS to unveil how the stereotype impacts them. Exploratory and confirmatory factor analyses (CFAs) supported a two-factor structure of the MMS-RS, namely negative responses to and positive endorsement of the MMS. Alongside the reliability estimates, the evidence for construct validity demonstrated that the MMS-RS has good psychometric properties. Interestingly, both negative reaction to and the positive endorsement of the MMS were found to coexist. Overall, the MMS-RS is a useful instrument for scholars who are interested in researching, intervening, and advocating for Asian Americans’ experiences with the MMS.